Xynthia: lessons learned from a catastrophe - Etienne Chauveau; Céline Chadenas; Bruno Comentale; Patrick Pottier; Amandine Blanlœil; Thierry Feuillet; Denis Mercier; Laurent Pourinet; Nicolas Rollo; Ion Tillier; Brice Trouillet (Cybergeo)
The storm Xynthia occurred on the 28th of february 2010. It has been one of the most deadly seen on the French territory since several decades, with 47 victims, half of them found on the department of Vendée. We suggest a global interpretation of the reasons of the disaster on two adjoining districts, in the south of this department, La Faute-sur-mer and L’Aiguillon-sur-mer. We first focus on the different natural hazard’s characteristics: wind’s strength, role of the high tide’s coefficients, topography of the affected coastal areas, particularly on enclosed bays and estuaries, constitute risk factors which have add their effects in time and space, creating strong uplifts of sea level. We then analyse the crisis development, which partially explains the vulnerability of specific areas. Following, the first economic consequences on submerged lands are presented. Finally, we point the lack of risk assessment, resulting from long and carelessness practices on territorial management, to the detriment of natural processes knowledge and constraints, especially on potentially submerged areas. The lack of risk awareness has persisted with decisions taken locally, as well as at the highest national politic power.Keywords: Xynthia, disaster, marine submersion, vulnerability, disaster remembrance, risk management